Methodology for assessment and analysis the geomechanical state of the opencast mining operations built up in the rock masses - Dachev Georgi; Kutsarov Kiril (Mining and Metallurgy Engineering Bor, 2019)
Ensuring the stability of constructive elements (rock flanks or benches) in the opencast pits and quarries is carried out in a different way, and this is often the reason of considering only separate parameters to be taken. Such assessments are often made using the different hypotheses and formulae such as those of Tsimbarevich, Fellenius, Maslov, Fisenko, etc. The key factors, influencing such assessments together and separately, are numerous and in most cases it is difficult to gather them together with one summarized formula. This paper presents a structured uniform methodology in order to provide an approach for assessment targeting the geomechanical state of the opencast mining operations , situated in the homogeneous rock masses.